Strategi pemelajaran bahasa pelajar sekolah menengah (Jurnal Bahasa, 2003)
This article describes the findings of a study on language learning strategies (LLS) employed by secondary school students. A comparison is made between strategies used by good and poor learners as well as strategies used by male and female students. A case study using a qualitative approach was used to find out the language learning strategies used by eight students. Four good learners and four poor learners representing both gender were chosen as subject for the study. The subject consist of Form Four students from a secondary school. An observation check list was used to find out as employed by the respondents while learning Bahasa Melayu in the classroom. Each subjects was observed for three periods each totaling 120 minutes of class time. The subjects were observed on their listening, speaking, reading and writing skills. Their behaviour were observed and recorded using an observation protocol developed form a pilot study. There results show that good learners used more as than poor learners; whereas, female students used more as than male students. In term of language skills, good female students and poor female students used more as in listening, reading and writing than their counterpart; while, good male students and poor male students used more LLS in speaking than their counterpart.